Changes in poisonings among adolescents in the UK between 1992 and 2012: a population based cohort study - Tyrrell, Edward G; Orton, Elizabeth; Tata, Laila J. (BMJ Publishing Group, 2016)
Background: Poisonings are a common cause of morbidity and mortality among adolescents. Yet surveillance data indicating current incidence rates (IRs) and time trends are lacking, making policy development and service planning difficult. We utilised population based primary care data to estimate adolescent poisoning rates according to intent across the UK. Methods: A cohort study of 1 311 021 adolescents aged 10–17 years, between 1992 and 2012, was conducted using routine primary care data from The Health Improvement Network. IRs and adjusted IRRs with 95% CIs were calculated for all poisonings, intentional, unintentional, unknown intent and alcohol related poisonings, by age, sex, calendar time and socioeconomic deprivation. Results: Overall poisoning incidence increased by 27% from the period 1992–1996 to 2007–2012, with the largest increases in intentional poisonings among females aged 16–17 years (IR 391.4/100 000 person years (PY), CI 328.9 to 465.7 for age 17 years in 1992–1996; 767.0/100 000 PY, CI 719.5 to 817.7 in 2007–2012) and alcohol related poisonings in females aged 15–16 years (IR 65.7/100 000 PY, CI 43.3 to 99.8 rising to 130.0/100 000 PY, CI 110.0 to 150.0 for age 15 years). A strong socioeconomic gradient for all poisonings persisted over time, with higher rates among the more deprived (IRR 2.63, CI 2.41 to 2.88 for the most vs least deprived quintile in 2007–2012). Conclusions: Adolescent poisonings, especially intentional poisonings, have increased substantially over time and remain associated with health inequalities. Social and psychological support for adolescents should be targeted at more deprived communities, and child and adolescent mental health and alcohol support service provision should be commissioned to reflect the changing need.